2003
DOI: 10.1097/00000658-200304000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: These data show that errors leading to laparoscopic bile duct injuries stem principally from misperception, not errors of skill, knowledge, or judgment. The misperception was so compelling that in most cases the surgeon did not recognize a problem. Even when irregularities were identified, corrective feedback did not occur, which is characteristic of human thinking under firmly held assumptions. These findings illustrate the complexity of human error in surgery while simultaneously providing insights. They dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
68
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 0 publications
2
68
1
Order By: Relevance
“…1,2 Hopefully today, this rate is much lower and ranges between 0.3% and 0.8% but remains two to three times up the injury rates reported for open cholecystectomy. 21 Considerable improvements in laparoscopic apparatus, better surgical training, advanced laparoscopic performance of almost all abdominal operations, and experience gained over the years are mostly responsible for this gratifying evolution.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…1,2 Hopefully today, this rate is much lower and ranges between 0.3% and 0.8% but remains two to three times up the injury rates reported for open cholecystectomy. 21 Considerable improvements in laparoscopic apparatus, better surgical training, advanced laparoscopic performance of almost all abdominal operations, and experience gained over the years are mostly responsible for this gratifying evolution.…”
Section: Discussionmentioning
confidence: 96%
“…1,2 Considerable improvements in the equipment and the technique itself, as well as training of residents in the laparoscopic technique, resulted in the progressive decrease of this incidence today. Nevertheless, it continues to be two to three times more common compared to published major bile duct injury rates for open cholecystectomy, 3,4 which indicates that this is still an incompletely resolved problem.…”
Section: Introductionmentioning
confidence: 99%
“…However, Way et al [21] reported that 97% of surgical accidents during laparoscopic cholecystectomy occurred as a result of visual misperceptions. Hofmeister et al [22] and Chan et al [2] also suggested that 2D display systems might cause optical illusions and erroneous maneuvers.…”
Section: Discussionmentioning
confidence: 99%
“…5,710 Studies in surgery using observational techniques and review of operative notes suggested that complications of laparoscopic cholecystectomy (e.g., bile duct injuries) and carotid endarterectomy were associated with situational awareness errors, especially involving perception. 5,7,8 In anesthesia, investigators in Australia 9 and Germany 10 reviewed voluntary critical incidents not resulting in patient injury and found a significant number of situational awareness errors (40 and 82%, respectively). In primary care 11 and nursing 12,13 situational awareness errors were studied qualitatively, but without quantitative data.…”
Section: Introductionmentioning
confidence: 99%